Radiological impact of natural radioactivity in Egyptian phosphate rocks, phosphogypsum and phosphate fertilizers. (May 2017) - El-Bahi, S.M.; Sroor, A.; Mohamed, Gehan Y.; El-Gendy, N.S.
Abstract: In this study, the activity concentrations of the natural radionuclides in phosphate rocks and its products were measured using a high- purity germanium detector (HPGe). The obtained activity results show remarkable wide variation in the radioactive contents for the different phosphate samples. The average activity concentration of 235 U, 238 U, 226 Ra, 232 Th and 40 K was found as (45, 1031, 786, 85 and 765 Bq/kg) for phosphate rocks, (28, 1234, 457, 123 and 819 Bq/kg) for phosphate fertilizers, (47, 663, 550, 79 and 870 Bq/kg) for phosphogypsum and (25, 543, 409, 54 and 897 Bq/kg) for single super phosphate respectively. Based on the measured activities, the radiological parameters (activity concentration index, absorbed gamma dose rate in outdoor and indoor and the corresponding annual effective dose rates and total excess lifetime cancer risk) were estimated to assess the radiological hazards. The total excess lifetime cancer risk (ELCR) has been calculated and found to be high in all samples, which related to high radioactivity, representing radiological risk for the health of the population. Highlights: Level of radioactivity of phosphate rocks and by-products samples. The radiological health hazard parameters. Radiological risk to the health of the population. The excess lifetime cancer risk factor.